Neurological and neuropsychological post-covid complications - Mielniczek, Katarzyna; Kowalska , Aleksandra; Jóźwik, Katarzyna; Lipiec, Marta; Dołomisiewicz , Diana (Journal of Education, Health and Sport, 2022)
Introduction: COVID-19 is an acute respiratory disease caused by the SARS-CoV-2 virus. It attacks the respiratory system in particular, however, it can also lead to gastrointestinal or neurological diseases. The disease leads to numerous neurological complications. Material and method: the purpose of this study is to review the neurological and neuropsychological complications that have arisen as a result of COVID-19 outbreak. The literature available on the PubMed scientific platform was reviewed. Time descriptors were set for 2020-2022. Results: Neurological symptoms are mainly due to cerebral hypoxia due to respiratory failure. These include encephalitis, meningitis, encephalopathies, seizures, disorders of consciousness, smell, taste and vision, among others. Neuropsychological complications can also occur. Conclusions: Pulmonary abnormalities, neurological complications and exercise intolerance were frequently identified complications among COVID-19 survivors. The main neurological symptoms reported were fatigue, concentration changes, memory loss, and sleep disturbances. In contrast, the longest-lasting complications were fatigue, loss of concentration or memory, weakness, pain and dizziness. Keywords: "COVID-19", "postcovid neurological symptoms", "neurological complications".